2020
DOI: 10.7759/cureus.8798
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Effects of Nut Consumption on Cardiovascular Biomarkers

Abstract: Background: Cardiovascular disease (CVD) is a leading cause of morbidity and mortality in the United States and changes in lifestyle can minimize the likelihood of succumbing to heart disease. Anti-inflammatory agents are commonly used to reduce the chronic inflammatory state behind the pathogenesis of CVD. Multiple studies have been published correlating nut consumption with a reduction in both heart attacks and strokes. The goal of this study is to determine to what extent the consumption of almonds, hazelnu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Replacing SFA with MUFA and PUFA helps reduce CVD and mortality (28) . It is equally necessary to take into account the beneficial effects of nuts on CVD risk factors, since earlier studies (36,37) have suggested that preventative influence of nuts on CVD and CHD likely stems from them (36) . For instance, a review of clinical trials found that nut consumption significantly reduced cholesterol concertation by 10•9 and TAG levels in patients with hypertriglyceridemia (38) .…”
Section: Discussionmentioning
confidence: 99%
“…Replacing SFA with MUFA and PUFA helps reduce CVD and mortality (28) . It is equally necessary to take into account the beneficial effects of nuts on CVD risk factors, since earlier studies (36,37) have suggested that preventative influence of nuts on CVD and CHD likely stems from them (36) . For instance, a review of clinical trials found that nut consumption significantly reduced cholesterol concertation by 10•9 and TAG levels in patients with hypertriglyceridemia (38) .…”
Section: Discussionmentioning
confidence: 99%
“…Walnuts possess a good quantity of phenolic compounds and thus play their part in minimizing inflammation. Nuts have explicitly demonstrated the anti‐inflammatory potential that was evident through a reduction in ESR levels after consumption of walnuts, almonds, and hazelnuts during four weeks trial (Adashek & Redding, 2020). In a similar study, the effect of epigallocatechin and MTX was investigated against adjuvant‐induced arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, nut intake increases the proportion of probiotic and butyrate-producing species which are associated with reduced microbially derived, proinflammatory secondary bile acids and LDL cholesterol [46,47]. Finally, regular nut consumption may also lead to a reduction in circulating levels of pro-inflammatory markers such as erythrocyte sedimentation rate (ESR), interleukin-6 (IL6), tumor necrosis factor-alpha (TNF-α) and C-reactive protein [49][50][51][52] which are associated with higher risk of cardio-vascular mortality and are usually elevated in NAFLD and implicated in its pathogenesis [53].…”
Section: Nut Consumption and Cardio-vascular Diseasementioning
confidence: 99%